Job loss-related complicated grief symptoms: A cognitive-behavioral framework - Van Eersel, Janske H. W.; Taris, Toon W.; Boelen, Paul A. (Frontiers in Psychiatry, 2022)
In a significant minority of people, involuntarily job loss can result in symptoms of job loss-related complicated grief (JLCG). The present cognitive-behavioural framework is introduced to explain the underlying processes that may lead to the development and maintenance of JLCG symptoms. Three core processes play a central role, namely (1) negative cognitions related to the job loss and misinterpretation of one’s grief reactions; (2) anxious and depressive avoidance strategies to cope with the job loss and its consequences; and (3) insufficient integration of the job loss into the autobiographical memory. These core processes are assumed to interact and reinforce each other, leading to JLCG symptoms. The three core processes can be influenced by certain risk factors, including circumstances surrounding the loss, personality traits, and characteristics of the social environment. JLCG symptoms can lead to additional psychological and practical problems, such as anxiety and depressive symptoms, lower employability, and reduced likelihood of re-employment. This paper explains and illustrates the three core processes with vignettes. Implications of the model for preventive measures and psychological interventions are introduced. It concludes with suggestions for future research on JLCG symptoms.